The quick-change artist : stories - Holladay, Cary C., 1958- (UPCC book collections on Project MUSE., 2006)
In these stories of magic and memory, clustered around a resort hotel in a small Virginia community, Cary Holladay takes the reader on an excursion through the changes wrought by time on the community and its visitors. From the quiet of a rural forest to the rhythms of rock and roll, The Quick-Change Artist is at once whimsical and hard-edged, dizzying in its matter-of-fact delivery of the fantastic. Romance, a sense of place and belonging, and the supernatural-especially in the lives of children coming of age-offer windows into worlds beyond the ordinary throughout The Quick-Change Artist.